2005
DOI: 10.1016/j.compchemeng.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics in multiphase distillation processes in packed towers

Abstract: In order to design packed columns for multiphase operation it is necessary to include reliable data on the flow behavior in the model. Since experiments inside packings are very difficult to perform, CFD simulations are considered to be a sensible approach as numerical experiments. To obtain reliable results validation is inevitable. We present the validation of two-and three-phase film flow under transient conditions. This application is not abundant in literature. Numerical results are compared to data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 10 publications
(6 reference statements)
4
78
0
1
Order By: Relevance
“…Under this condition, simulations are carried out with different mesh sizes of 0.1mm, 0.0625mm and 0.05mm along the film thickness. A comparison of the specific wetted area between experimental data (Hoffmann et al, 2005) and simulation results with different mesh sizes for cases 1-5 are shown in Fig. 3.…”
Section: Determination Of the Mesh Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Under this condition, simulations are carried out with different mesh sizes of 0.1mm, 0.0625mm and 0.05mm along the film thickness. A comparison of the specific wetted area between experimental data (Hoffmann et al, 2005) and simulation results with different mesh sizes for cases 1-5 are shown in Fig. 3.…”
Section: Determination Of the Mesh Sizementioning
confidence: 99%
“…Detailed descriptions about the experimental setup and operating procedure could be found in Hoffmann et al (2005) and Ausner (2006). To reduce the influence of the outflow field and the gas pressure on the liquid phase, the height of the channel for simulations is fixed at 10mm (usually the film thickness δ is not more than 1mm corresponding to the current Reynolds numbers).…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the separation efficiency of the structured packed column highly depends on the flow behavior on the surface of the packings. It has been known that the liquid flow behavior such as film, rivulet and droplet flow only occurs in a few inches inside the packing and is governed by the liquid and gas loads as well as by system parameters like the contact angle [1]. The fluid dynamics is therefore a deterministic issue not only from the viewpoint of the basic hydrodynamics but also because of its influence on interfacial heat and mass transfer rates in distillations.…”
Section: Introductionmentioning
confidence: 99%
“…The volume-of-fluid-like model in CFX 5.0 was utilized to study the same. The influence of surface tension was taken into account, and the simulation studies were validated with experimental work [10][11][12][13].…”
Section: Cfd Studiesmentioning
confidence: 99%